(3TQM bhGYO cGTa GdZWGAs - (3GdLfGMj, GdfLaj, GdeGdcj, LYaQ Hf NVQ cGTa GdZWGA, J (B1226(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj GTJb fhQ GdhLhO ef XdeI GdYOe(B... (3CeG HYO, aEfg cGf jNJdL aj NGWQj (B... (3bhGYO GdYdGeI TQMG HgG dGFb(B...s
(3BNQgG (B:s
(3hMce GdYQa cMe Gdcjd hGdhRf hZjQgeG(B... (3EPG cGf eLghd GdbOQ hCdG jLgd bOQg LGR HjYg HLfSgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
(3GdCYdGe(B: (3L(B2(3, U(B124s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis